Småskalig utsädesproduktion - Schmiterlöw, Henrik (2006)
The economic situation in the Swedish agricultural industry is currently experiencing a development towards larger units. This progress occurs simultaneously as farmers in cooperation more frequently make investments to decrease risk exposure and to improve the financial result. The purpose with this thesis is to study which advantages and problems a group of farmers experience after a common investment in a small-scale seed production. The aim with this investment is to increase the level of vertical integration in their respective agricultural firms and the results will be analyzed from an economic point of view. At present, the farmers are all seed producers with considerable cultivation areas. They experience that the co it of inputs are getting higher and higher. Further refining the goods produced means that the farmers produce certified seed in a common plant, for own use and for sale.